Pengaruh Kunjungan Wisatawan, Inflasi Dan Kurs Dollar Amerika Serikat Terhadap Ekspor Anyamandi Provinsi Bali - Sudarma, Putu Agus; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
This study aims to determine the effect of tourist visits, inflation and the dollar exchange rate against the United States exports of woven in the province of Bali. This research was conducted in the province of Bali. The data used in this research is secondary data. Data analysis technique used is multiple linear regression analysis. The data collection is done by non-participant observation. Methods of data collection is done by studying some of the descriptions of books and journals as well as through intansi related. Then the data is processed by using multiple linear regression analysis using the Test F and Test T. The analysis showed that the variables of tourist arrivals and US dollar exchange rate has positive influence on the export of woven province of Bali. Inflation negative effect on exports of woven province of Bali. US dollar exchange rate has positive influence on the export of woven province of Bali. With most dominant variable is the US dollar exchange rate.
Keywords: Visits Travelers, inflation, exchange rate US Dollar, Export Woven Bali Province